2015
DOI: 10.5897/ajmr2014.7068
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B virus in a tertiary institution in North Western Nigeria

Abstract: Hepatitis B virus (HBV) is endemic in sub-Saharan Africa. The study was conducted to determine the seroprevalence of HBV infection and the possible potential risk factors among students of Ahmadu Bello University, Zaria, Kaduna State, Nigeria. A cross-sectional study was conducted between April and August, 2013. Structured questionnaires were administered to obtain socio demographic data and possible risk factors that might be associated with the viral infection. Blood samples were collected at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
7
12
3
Order By: Relevance
“…Such records include prevalence of 6.0% recorded among students of the Federal university of wukari, Taraba state, Nigeria (Imaren ezor et al, 2016), 4.5% recorded among students of university of Maiduguri in Nigeria (Dawurang et al, 2012) and 12.5% reported among asymptomat ic students in Ahmadu Bello Un iversity, Zaria (A minu et al, 2013). Also, the prevalence rate of 9.5% reported in a population of students at Ladoke Akintola Un iversity of Technology in south west Nigeria (Mabayoje et al, 2010), 9.2% recorded in Ahmadu Bello university, Zaria, Kaduna State, Nigeria (Isa et al, 2015); and 13.2% recorded in Nassarawa State Univers ity in Keffi, Nigeria (Pennap et al, 2010) for HBsAg are all lower than the prevalence rate recorded in this study for HBV antibodies. The reason is that while these researchers investigated randomly selected subjects irrespective of risk exposure, this s tudy focused only on a group of subjects with sexual risk behavior only .…”
Section: Result:-contrasting
confidence: 55%
“…Such records include prevalence of 6.0% recorded among students of the Federal university of wukari, Taraba state, Nigeria (Imaren ezor et al, 2016), 4.5% recorded among students of university of Maiduguri in Nigeria (Dawurang et al, 2012) and 12.5% reported among asymptomat ic students in Ahmadu Bello Un iversity, Zaria (A minu et al, 2013). Also, the prevalence rate of 9.5% reported in a population of students at Ladoke Akintola Un iversity of Technology in south west Nigeria (Mabayoje et al, 2010), 9.2% recorded in Ahmadu Bello university, Zaria, Kaduna State, Nigeria (Isa et al, 2015); and 13.2% recorded in Nassarawa State Univers ity in Keffi, Nigeria (Pennap et al, 2010) for HBsAg are all lower than the prevalence rate recorded in this study for HBV antibodies. The reason is that while these researchers investigated randomly selected subjects irrespective of risk exposure, this s tudy focused only on a group of subjects with sexual risk behavior only .…”
Section: Result:-contrasting
confidence: 55%
“…A sero positivity of 1.10% and 0.58% was reported amongst the hospital attendees from Warudi in Nashik, (20) and Tumkuru, South India (21) . On the contrary, in a retro-prospective study conducted at a hospital in Nepal and a tertiary care hospital at North Western Nigeria seroprevelance of 4.19% (22) and 9.2% (23) has been reported. In another pivotal study conducted at a North Indian Hospital from 2005-2013 seroprevelance was found to range from 0.92% to 1.75% (24) indicative of consistent infection.…”
Section: Resultsmentioning
confidence: 88%
“…Micro-Point Rapid Diagnostic Test Kit (Made in USA) was used to test for the presence of anti-HAV IgM. All results were read and interpreted according to the manufacturer's instructions [19,20]. Results were tabulated according to demographic factors as shown in Table 1, Table 2, Table 3, Table 4, Table 5, Table 6 and Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 300 samples were collected based on a previous related prevalence rate of 18% for HBV obtained from the formula for sample size estimation in prevalence studies given by: [18,19].…”
Section: Methodsmentioning
confidence: 99%